EFFECT OFLEADERSHIP, ORGANIZATIONAL CULTUREANDJOB SATISFACTIONOFORGANIZATIONAL CITIZENSHIP BEHAVIOR(OCB) TO EMPLOYEESINPTBATAVIAPROSPERINDO FINANCE, TBKJAKARTA - Ulfa, Mairiyah (Fakultas Ekonomi, Universitas Negeri Jakarta, 2016)
In this study,the author investigate the relationship of leaderhip, organization culture and work satisfaction toward organizational citizenship behavior on employee in PT Batavia Prosperindo Finance,Tbk. In the company’s life, there are several holders an important role in the company itself. Employee can give a contribution to productivity in the firm by extra role without compentation.Researcher use leadership, organization culture, work satisfaction, and also OCB as the variables. Researcher use SPSS version 22 to descriptive analyses and also structural equation model (SEM) by lisrel 8.8 software. The research show there is influence leadership, organizational culture and work satisfaction to OCB on employee with R determination 0,43. Keywords: leadership, organization culture, work satisfaction and OCB